The Impact of Price Discount, Free Shipping, and Live Streaming on Consumer Purchase Intention on Tiktok Shop - Rizka Salsabila; Andri Soemitra; Siti Aisyah (Universitas Sebelas Maret, 2024)
Due to the rapid growth of the footwear market in Indonesia, both domestic and foreign shoe manufacturers face increasingly fierce competition. To remain competitive, shoe manufacturers must be able to innovate, especially in marketing. This research examines the impact of three independent factors, namely Price Discount, Live streaming, and Free Shipping, on consumer purchase interest in Ventela shoe products on the TikTok Shop platform among students in Medan. This research uses a quantitative approach to evaluate the theory by examining the relationship between variables. Information for research purposes was collected from respondents through questionnaires. Data was analyzed using SPSS version 29 analysis tools. The research population consists of students in Medan City who use the TikTok application and about Ventela shoe products, with a sample of 97 respondents selected through a non-probability sampling method. The questionnaire data were analyzed using multiple linear regression. This research shows that price discounts, free shipping, and live streaming have a positive or significant effect on consumer buying interest. The findings of this research provide a better understanding of the things that impact purchasing interest in terms of discounts, live streaming, and free shipping for Ventela shoe products on the TikTok Shop. These findings can help develop better marketing strategies focusing on increasing customer interest.Keywords: consumer purchase interest; footwear market competition; marketing innovation; tiktok shop strategy